Patterns of diffusion kurtosis changes in Parkinson's disease subtypes - Sejnoha Minsterova, Alzbeta; Klobusiakova, Patricia; Pies, Adrian; Galaz, Zoltan; Mekyska, Jiri; Novakova, Lubomira; Nemcova Elfmarkova, Nela; Rektorova, Irena (Parkinsonism & related disorders, 2020)
BACKGROUND: Diffusion kurtosis imaging has been applied to evaluate white matter and basal ganglia microstructure in mixed Parkinson's disease (PD) groups with inconclusive results. OBJECTIVES: To evaluate specific patterns of kurtosis changes in PD and to assess the utility of diffusion imaging in differentiating between healthy subjects and cognitively normal PD, and between PD with and without mild cognitive impairment. METHODS: Diffusion scans were obtained in 92 participants using 3T MRI. Differences in white matter were tested by tract-based spatial statistics. Gray matter was evaluated in basal ganglia, thalamus, hippocampus, and motor and premotor cortices. Brain atrophy was also assessed. Multivariate logistic regression was used to identify a combination of diffusion parameters with the highest discrimination power between groups. RESULTS: Diffusion kurtosis metrics showed a significant increase in substantia nigra (p = 0.037, Hedges' g = 0.89), premotor (p = 0.009, Hedges' g = 0.85) and motor (p = 0.033, Hedges' g = 0.87) cortices in PD with normal cognition compared to healthy participants. Combined diffusion markers in gray matter reached 81% accuracy in differentiating between both groups. Significant white matter microstructural changes, and kurtosis decreases in the cortex were present in cognitively impaired versus cognitively normal PD. Diffusion parameters from white and gray matter differentiated between both PD phenotypes with 78% accuracy. CONCLUSIONS: Increased kurtosis in gray matter structures in cognitively normal PD reflects increased hindrance to water diffusion caused probably by alpha-synuclein-related microstructural changes. In cognitively impaired PD, the changes are mostly driven by decreased white matter integrity. Our results support the utility of diffusion kurtosis imaging for PD diagnostics.
Keywords: Mild cognitive impairment; šedá hmota; logistické modely; zobrazování difuzních tenzorů; hipokampus; Cognitive Dysfunction; Female; Models, Statistical; Parkinsonova nemoc; multivariační analýza; ženské pohlaví; Logistic Models; Multivariate Analysis; Gray Matter; White Matter; difuzní magnetická rezonance; lidé; Motor Cortex; statistické modely; Thalamus; bazální ganglia; mozek; atrofie; Diagnostic marker; Male; Aged; Atrophy; motorické korové centrum; thalamus; Brain; Diffusion kurtosis imaging; Diffusion Tensor Imaging; Diffusion Magnetic Resonance Imaging; Parkinson's disease; kognitivní dysfunkce; Basal Ganglia; Hippocampus; lidé středního věku; senioři; mužské pohlaví; MRI; Middle Aged; bílá hmota; Parkinson Disease; Humans